Evaluation of the Impact of Changes to the Airport Road Masterplan on Traffic Performance (Case Study of Hang Nadim Airport, Batam City) - Firsya Odira; Yusra Aulia Sari (Journal of Civil Engineering and Planning (JCEP), 2025)
Batam City experienced increased congestion on several main roads, especially in the Hang Nadim Airport area. To overcome this, the government made changes to the road master plan. After the masterplan changes, the road capacity increased from 2,944.92 pcu/hour to 7,438.2 pcu/hour. Traffic volume from the Airport-Nagoya direction was recorded at 3,111.1 pcu/hour and from the Nagoya-Nongsa direction at 2,415.2 pcu/hour. The study was only conducted in areas with frequently passed traffic volume capacity, namely the Airport-Nagoya direction and the Nagoya-Nongsa direction. The evaluation was performed using indicators of capacity, traffic volume, and road service level. These results provide an important basis for more adaptive airport transportation planning in the future.